Resillient Living by Optimizing the Building Façade in Designing Post-covid Housing - Elina Mohd Husini; Juliza Jamaludin; Fadli Arabi; Shaza Liyana Shamri; Azhani Abdul Manaf; Madihah Mat Idris (Planning Malaysia, 2024)
Indexed by Scopus/MyCite